(untitled) (Jurnal Pustaka, 2026)
Sex education for teenagers and children is considered crucial in today’s modern society. In an easily accessible information era, the risk of receiving inappropriate information about sex is higher for children and teenagers. Therefore, timely and age-appropriate sex education is seen as a safeguard against such dangers. Sex education not only provides biological information but also encompasses moral, ethical, and religious aspects, especially in the context of Islam. The Quran and Sunnah serve as a foundation for sex education, not considered taboo but introduced wisely according to a child’s development. The importance of early sex education is evident from a psychological perspective, where gradual education aligns with a child’s developmental stages in managing physical and emotional changes during adolescence. In developing this article, a qualitative method was chosen with a literature research approach. This approach allows understanding the topic in a natural and non-experimental context, consistent with a personal and contextual approach to sex education. Literature sources such as scientific books, research reports, dissertations, theses, articles in scientific journals, encyclopedias, regulations, decisions, and other scientific written sources were used as a strong theoretical basis. Information gathered from these sources supports claims about the urgency of sex education aligned with religious and moral values. This article provides a solid foundation to comprehend and develop sex education that corresponds to a child’s development, with the aim of nurturing individuals who are sexually aware and responsible.